Presentation. (Tokyo : Tokyo University of the Arts, 1989)
Yoshio, Ogawa ; Atsushi, Ohta ; Hiroshi, Kasahara ; Ken, Kageyama ; Takahito, Kiriyama ; Takahide, Koike ; Yoichi, Sakamaki ; Hiroyuki, Saito ; Takashi, Sato ; Katsuhiko, Sekine ; Tomoko, Sugahara ; Fuminori ; Terakubo ; Ayumi, Tonokura ; Hideki, Nagahashi ; Goro, Hirata ; Ryosuke, Fukushi ; Isao, Fujii ; Yuki, Matsumoto
Presentation, Tokyo University of the Arts, Tokyo, 1989
Catalogus: Text Japanese - Bijlage: Text English
kunstcatalogus